Multilayer composite barrier film and preparation method thereof
By adopting a multi-layer composite barrier film structure, including polyethylene terephthalate substrate layer, inorganic plating, barrier coating and adhesive layer, the high cost and low efficiency of high gas barrier film preparation in the prior art is solved. The problem is to achieve both high gas barrier performance and industrial production.
Patent Information
- Application Number
- CN202311024780.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-14
- Publication Date
- 2025-02-21
AI Technical Summary
In the prior art, when preparing high-gas barrier films, the equipment cost is high and the production efficiency is low. Repeated coating and coating processes are likely to damage the inorganic layer, resulting in reduced barrier performance, complex process and high cost.
Adopt a multi-layer composite barrier film structure, including polyethylene terephthalate substrate layer, inorganic plating, barrier coating, adhesive layer, barrier coating, inorganic plating and polyethylene terephthalate substrate layer , bond it together through a simple process, reduces water vapor transmittance (WVTR) and is suitable for industrial mass production.
It has achieved the improvement of high gas barrier performance, simplified production processes, reduced production costs, and provided a multi-layer composite barrier film suitable for industrial mass production.
Smart Images

Figure CN119489606A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a gas barrier film required for use in the fields of food and medicine packaging, solar cell encapsulation, etc., which require high gas barrier properties. Background Art
[0002] On the surface of the organic polymer substrate, a layer of inorganic oxide / nitride film with a thickness of nanometer level is added by PVD (resistance thermal evaporation, electron evaporation, magnetron sputtering) or CVD method. The inorganic film is highly transparent and has a high gas barrier effect. It is often used as a packaging material for food and medicine to block various gases such as water vapor, oxygen, carbon dioxide, and aroma, as well as a packaging component for solar cells, OLEDs, etc.
[0003] In order to achieve the goal of high barrier, in the traditional multi-layer organic / inorganic stacked barrier film technology, the inorganic layer is generally prepared by production methods such as magnetron sputtering or PECVD, which has high equipment cost and low production efficiency. The inorganic layer prepared by high-efficiency evaporation coating often has many defects and cannot achieve the barrier performance we need. Therefore, it is necessary to perform a plating-coating process on the same substrate and repeat it many times to achieve a multi-layer structure. However, in the repeated plating and coating process, it is very easy to damage the plated inorganic layer, which destroys the structure of the coating itself and reduces the barrier performance. In addition, the production process is complicated by plating-coating-plating-coating on the same substrate, which also increases the production cost.
[0004] Therefore, in view of the shortcomings of the current solutions, we fully utilized the existing technology, bonded the two polyethylene terephthalate layers / inorganic coatings / barrier coatings together with an adhesive, and used a simple process to achieve a reduction of WVTR by nearly an order of magnitude, providing a new idea for multi-layer composite barrier films that can be directly used for large-scale industrial production. Summary of the invention
[0005] The object of the present invention is to provide a multi-layer composite barrier film and a preparation method thereof to solve the problems raised in the above background technology.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] A multi-layer composite barrier film comprises a polyethylene terephthalate substrate layer, an inorganic coating layer, a barrier coating layer, an adhesive layer, a barrier coating layer, an inorganic coating layer, and a polyethylene terephthalate substrate layer, which are composited in sequence from bottom to top, with a total of seven layers.
[0008] Preferably, the overall thickness of the barrier film is less than 250 μm, and the total thickness of the barrier film excluding the organic flexible substrate is less than 50 μm.
[0009] Preferably, the thickness of the single-layer polyethylene terephthalate substrate layer is in the range of 12 to 100 μm.
[0010] Preferably, the thickness of the single-layer inorganic coating is in the range of 10-100 nm.
[0011] Preferably, the thickness of the single-layer barrier coating is in the range of 0.5-10 μm.
[0012] Preferably, the thickness of the bonding layer is in the range of 0.5-5 μm.
[0013] Preferably, the inorganic coating is one or two of oxides such as SiOx, AlOx, SnOx, and ZnOx.
[0014] Preferably, the barrier coating is one or two of acrylic resin, polyurethane, organic modified ceramics, organic-inorganic hybrid polymers, polysiloxane-acrylic composite resins, and polysiloxane-polyurethane composite resins.
[0015] Preferably, the adhesive component of the adhesive layer can use a common adhesive, and its type is not particularly limited, such as polyether adhesive, polyester adhesive, polyurethane adhesive, vinyl adhesive, acrylic adhesive, polyamide adhesive, epoxy adhesive, etc.
[0016] A method for preparing a multi-layer composite barrier film, the method comprising the following steps:
[0017] 1) The inner surface of the upper and lower polyethylene terephthalate layers is corona treated to ensure that the dyne value is greater than 54;
[0018] 2) coating an inorganic coating layer on the polyethylene terephthalate layer by PVD (resistance thermal evaporation, electron evaporation, magnetron sputtering) or CVD method, wherein the thickness of the inorganic layer is 10-100 nm;
[0019] 3) Apply a barrier coating on top of the inorganic layer by roll-to-roll coating. The thickness of the barrier coating is 0.5-10 μm. The barrier coating is thermally cured for 8-15 seconds at a temperature of 80-130°C, and then cured.
[0020] 4) Applying an adhesive on the lower barrier coating, compounding the film with the upper barrier layer thereon, and then aging.
[0021] 5) The oxygen and water vapor permeabilities of the prepared barrier film were tested using a Labthink C390H water vapor permeability tester and a C103M gas permeability tester, and the light transmittance of the film was tested using a U-Tech T2600 UV spectrophotometer. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 is a schematic diagram of a multi-layer composite barrier film of the present invention;
[0023] Figure 2 The present invention is a flow chart of a method for preparing a multi-layer composite barrier film. DETAILED DESCRIPTION
[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] The embodiment of the present invention provides a flexible transparent ultra-low water vapor transmission rate barrier film, such as Figure 1 As shown, a multi-layer composite barrier film includes a polyethylene terephthalate substrate layer, an inorganic coating layer, a barrier coating layer, an adhesive layer, a barrier coating layer, an inorganic coating layer, and a polyethylene terephthalate substrate layer, which are composited in sequence from bottom to top, with a total of seven layers.
[0026] The overall thickness of the barrier film is less than 250 μm, and the total thickness of the barrier film excluding the organic flexible substrate is less than 50 μm.
[0027] The thickness of the single polyethylene terephthalate substrate layer is in the range of 12 to 100 μm.
[0028] The thickness of the single-layer inorganic coating is in the range of 10-100 nm.
[0029] The thickness of the single-layer barrier coating is in the range of 0.5-10 μm.
[0030] The thickness of the adhesive layer is in the range of 0.5-5 μm.
[0031] Inorganic coating The inorganic coating is one or two of oxides such as SiOx, AlOx, SnOx, and ZnOx.
[0032] The barrier coating is one or two of acrylic resin, polyurethane, organic modified ceramics, organic-inorganic hybrid polymer, polysiloxane-acrylic composite resin, and polysiloxane-polyurethane composite resin.
[0033] The adhesive of the adhesive layer may be a common adhesive, and its type is not particularly limited, for example, polyether adhesive, polyester adhesive, polyurethane adhesive, vinyl adhesive, acrylic adhesive, polyamide adhesive, epoxy adhesive, etc.
[0034] like Figure 2 As shown, a method for preparing a flexible transparent ultra-low water vapor transmission rate barrier film comprises the following steps:
[0035] 1) corona discharge is performed on the inner surfaces of the upper and lower polyethylene terephthalate layers to ensure that the dyne value is greater than 54; 2) an inorganic coating is plated on the polyethylene terephthalate layer by PVD (resistance thermal evaporation, electron beam evaporation, magnetron sputtering) or CVD method, and the thickness of the inorganic layer is 10-100 nm;
[0036] 3) applying a barrier coating on the inorganic layer by roll-to-roll coating, the barrier coating thickness is 0.5-10 μm, thermally curing the barrier coating for 8-15 seconds at a temperature of 80-130° C., and then performing a curing treatment;
[0037] 4) applying an adhesive on the lower barrier coating, compounding the film with the upper barrier layer thereon, and then aging;
[0038] 5) The oxygen and water vapor permeability of the prepared barrier film were tested using Labthink C390H water vapor permeability tester and C103M gas permeability tester, and the light transmittance of the film was tested using U-Tech T2600 UV spectrophotometer.
[0039] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively in combination with the embodiments and drawings below. However, the specific embodiments are only used to explain the present invention, and the present invention is not limited to the embodiments described herein.
[0040] Example 1: The inner surface of the upper and lower polyethylene terephthalate layers (a, b) with a thickness of 35 μm is corona-treated to ensure that the dyne value is greater than 54, and a layer of Al is plated on the polyethylene terephthalate layers (a, b) by resistive thermal evaporation. Ox, the thickness of the inorganic layer is 10nm; on the inorganic layer (a, b), an organic-inorganic hybrid polymer coating is coated by roll-to-roll coating, the thickness of the barrier coating is 1μm, the barrier coating is thermally cured for 15s at a temperature of 120°C, and then aged at 80°C / 24h; an acrylic resin adhesive is coated on the barrier coating (a), and the film (b) is compounded therewith, and then aged for 24h at a temperature of 50°C; the oxygen and water vapor permeabilities of the prepared barrier film are tested using a Labthink C390H water vapor permeability tester and a C103M gas permeability tester, and the light transmittance of the film is tested using a U-Tech T2600 UV spectrophotometer.
[0041] Example 2: The inner surface of the upper and lower polyethylene terephthalate layers (a, b) with a thickness of 35 μm is subjected to corona treatment to ensure that the dyne value is greater than 54, and a layer of S is deposited on the polyethylene terephthalate layers (a, b) by electron beam evaporation. iOx, the thickness of the inorganic layer is 40nm; on the inorganic layer (a, b), an organic-inorganic hybrid polymer coating is coated by roll-to-roll roller coating, the thickness of the barrier coating is 1μm, the barrier coating is thermally cured for 15s at a temperature of 120°C, and then aged at 80°C / 24h; an acrylic resin adhesive is coated on the barrier coating (a), and the film (b) is compounded therewith, and then aged for 24h at a temperature of 50°C; the oxygen and water vapor permeabilities of the prepared barrier film are tested using a Labthink C390H water vapor permeability tester and a C103M gas permeability tester, and the light transmittance of the film is tested using a U-Tech T2600 UV spectrophotometer.
[0042] Example 3: The inner surface of the upper and lower polyethylene terephthalate layers (a, b) with a thickness of 35 μm is subjected to corona treatment to ensure that the dyne value is greater than 54, and a layer of Al is plated on the polyethylene terephthalate layers (a, b) by resistive thermal evaporation. Ox, the thickness of the inorganic layer is 10nm; on the inorganic layer (a, b), an organic-inorganic hybrid polymer coating is coated by roll-to-roll roller coating, the barrier coating thickness is 1μm, the barrier coating is thermally cured for 15s at a temperature of 120°C, and then aged at 120°C / 2h; an acrylic resin adhesive is coated on the barrier coating (a), and the film (b) is compounded therewith, and then aged for 24h at a temperature of 50°C; the oxygen and water vapor permeabilities of the prepared barrier film are tested using a Labthink C390H water vapor permeability tester and a C103M gas permeability tester, and the light transmittance of the film is tested using a U-Tech T2600 UV spectrophotometer.
[0043] Example 4: The inner surface of the upper and lower polyethylene terephthalate layers (a, b) with a thickness of 35 μm is subjected to corona treatment to ensure that the dyne value is greater than 54, and a layer of S is deposited on the polyethylene terephthalate layers (a, b) by electron beam evaporation. iOx, the thickness of the inorganic layer is 40nm; on the inorganic layer (a, b), an organic-inorganic hybrid polymer coating is coated by roll-to-roll roller coating, the thickness of the barrier coating is 1μm, the barrier coating is thermally cured for 15s at a temperature of 120°C, and then aged at 120°C / 2h; an acrylic resin adhesive is coated on the barrier coating (a), and the film (b) is compounded therewith, and then aged for 24h at a temperature of 50°C; the oxygen and water vapor permeabilities of the prepared barrier film are tested using a C390H water vapor permeability tester and a C103M gas permeability tester from Labthink, and the light transmittance of the film is tested using a T2600 UV spectrophotometer from Uco Instrument.
[0044] Example 5: The inner surface of the upper and lower polyethylene terephthalate layers (a, b) with a thickness of 35 μm is subjected to corona treatment to ensure that the dyne value is greater than 54, and a layer of Al is plated on the polyethylene terephthalate layers (a, b) by resistive thermal evaporation. Ox, the thickness of the inorganic layer is 10nm; on the inorganic layer (a, b), a polyurethane barrier coating is applied by roll-to-roll coating, the thickness of the barrier coating is 1μm, the barrier coating is thermally cured for 10s at a temperature of 100°C, and then aged at 55°C / 48h; an acrylic resin adhesive is applied on the barrier coating (a), and the film (b) is compounded therewith, and then aged for 24h at a temperature of 55°C; the oxygen and water vapor permeabilities of the prepared barrier film are tested using a Labthink C390H water vapor permeability tester and a C103M gas permeability tester, and the light transmittance of the film is tested using a U-Tech T2600 UV spectrophotometer.
[0045] Example 6: The inner surface of the upper and lower polyethylene terephthalate layers (a, b) with a thickness of 35 μm is corona-treated to ensure that the dyne value is greater than 54, and a layer of S is deposited on the polyethylene terephthalate layers (a, b) by electron beam evaporation. iOx, the thickness of the inorganic layer is 40nm; on the inorganic layer (a, b), a polyurethane barrier coating is applied by roll-to-roll coating, the thickness of the barrier coating is 1μm, the barrier coating is thermally cured for 10s at a temperature of 100°C, and then aged at 55°C / 48h; an acrylic resin adhesive is applied on the barrier coating (a), and the film (b) is compounded therewith, and then aged for 24h at a temperature of 55°C; the oxygen and water vapor permeabilities of the prepared barrier film are tested using a C390H water vapor permeability tester and a C103M gas permeability tester from Labthink, and the light transmittance of the film is tested using a T2600 UV spectrophotometer from Uco Instrument.
[0046] The following is a table of test data of WVTR and light transmittance of various embodiments:
[0047]
[0048] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A multi-layer composite barrier film, characterized in that: The multi-layer composite barrier film structure comprises an intermediate layer and polyethylene terephthalate layers respectively arranged on the upper and lower sides of the intermediate layer. The intermediate layer is composed of an inorganic coating layer, a barrier coating layer and an adhesive layer.
2. The multi-layer composite barrier film according to claim 1, characterized in that: The thickness of the polyethylene terephthalate layers on the upper and lower sides is 12-100 μm respectively.
3. The multi-layer composite barrier film according to claim 1, characterized in that: The intermediate layer is composed of the following layers in terms of thickness: Inorganic coating 10-100nm Barrier coating 0.5-10μm Adhesive layer 0.5-5μm.
4. The multi-layer composite barrier film according to claim 1 or 3, characterized in that: The inorganic coating is one or two of oxides such as SiOx, AlOx, SnOx, and ZnOx.
5. The multi-layer composite barrier film according to claim 1 or 3, characterized in that: The barrier coating is one or two of acrylic resin, polyurethane, organic modified ceramics, organic-inorganic hybrid polymer, polysiloxane-acrylic composite resin, and polysiloxane-polyurethane composite resin.
6. The multi-layer composite barrier film according to claim 1 or 3, characterized in that: The adhesive component of the adhesive layer may be any common adhesive, and its type is not particularly limited, such as polyether adhesive, polyester adhesive, polyurethane adhesive, vinyl adhesive, acrylic adhesive, polyamide adhesive, epoxy adhesive, etc.
7. A method for preparing a multi-layer composite barrier film according to claim 1, characterized in that: The preparation method comprises the following steps: 1) Perform corona treatment on the upper and lower polyethylene terephthalate layers to ensure that their dyne values are greater than 54; 2) coating an inorganic coating layer on the polyethylene terephthalate layer by PVD (resistance thermal evaporation, electron beam evaporation, magnetron sputtering) or CVD method, wherein the thickness of the inorganic layer is 10-100 nm; 3) Applying a barrier coating on top of the inorganic layer by roll-to-roll coating, with a thickness of 0.5-10 μm; 4) Applying an adhesive on one of the barrier coating layers, attaching another barrier layer thereto and then curing the layers. 5) The oxygen and water vapor permeability of the barrier film were tested using a C390H water vapor permeability tester and a C103M gas permeability tester from Labthink. The light transmittance of the film was tested using a T2600 UV spectrophotometer from U-Tech.
8. The method for preparing a multi-layer composite barrier film according to claim 7, characterized in that: When coating the barrier layer, a thermosetting coating is selected, the drying temperature is 80-130°C, and the curing temperature is 50-100°C.
9. According to the method for preparing a multi-layer composite barrier film according to claim 7, the bonding layer is a thermoplastic adhesive.
10. According to the method for preparing a multi-layer composite barrier film as claimed in claim 7, after bonding and ripening the polyethylene terephthalate layer with the intermediate layer, the final multi-layer composite barrier film can be obtained, and its optimal water vapor transmission rate is less than 0.1g / m2 / day, and the oxygen transmission rate is less than 0.1cm3 / m2 / day.
Citation Information
Cited By
Degradable polylactic acid ultrahigh-barrier packaging film and preparation method thereof
CN121777550A